IMPROVING THE PENAL INSTITUTION IN THE CRIMINAL LAW OF UZBEKISTAN - Qunduz Rozimova (Modern American Journals, 2025)
This article analyzes some features of improving the penal institution for criminal offenses in Uzbekistan's criminal law. In particular, the theoretical views of scientists on the commission of several crimes and recidivism are studied. At the end of the article, the author developed proposals to improve criminal law in this area.
Keywords: Criminal law, punishment, multiple crimes, recidivism, judgement, conviction and more.